2020
DOI: 10.1021/acsomega.0c02516
|View full text |Cite
|
Sign up to set email alerts
|

Yb(OTf)3-Catalyzed and Di-tert-butyl Dicarbonate-Mediated Decarboxylative Etherification and Esterification Reactions

Abstract: Protecting group chemistry has invariably captured the fascination of chemists because of its extensive viability in chemical synthesis. The present report describes our pioneer work of applying ytterbium triflate as a catalyst, for the reaction of alcohols with di- tert -butyl dicarbonate (Boc 2 O) leading to the formation of tert -butyl ethers. There exists no recorded evidence for the use of Yb(OTf) 3 as a catalyst f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Rare-earth elements (REEs), possessing unique electronic and magnetic properties, constitute an indispensable group of elements essential across various fields, such as electronic devices, permanent magnets, sensors, and catalysts. While the global demand for REEs continues to increase, , the worldwide reserves of these elements remain limited . Moreover, the recovery of REEs from their natural deposits and various secondary feedstocks, and subsequent separation face major challenges due to their similar physicochemical properties .…”
Section: Introductionmentioning
confidence: 99%
“…Rare-earth elements (REEs), possessing unique electronic and magnetic properties, constitute an indispensable group of elements essential across various fields, such as electronic devices, permanent magnets, sensors, and catalysts. While the global demand for REEs continues to increase, , the worldwide reserves of these elements remain limited . Moreover, the recovery of REEs from their natural deposits and various secondary feedstocks, and subsequent separation face major challenges due to their similar physicochemical properties .…”
Section: Introductionmentioning
confidence: 99%
“…Replacing 2 with diethyl carbonate ( 6) failed to provide the desired product, revealing that diethyl carbonate can not participate in the reaction. [24] Based on the literature [25] and our preliminary studies, we proposed the reaction mechanism shown in Scheme 4. The reaction is likely initiated by oxidative addition of the CÀ O bond of 2 to rhodium(I) species A followed by extrusion of CO 2 .…”
mentioning
confidence: 99%